EDUCATIONAL VALUES IN THE NOVEL “PANGERAN HATI” BY MELLYANA DHIAN - Wa Ode Shinta Cahyani Belavori; La Ode Sahidin; Saidiman (Jurnal Casa Cendekia, 2026)
The purpose of this research is to describe what education value are contained in Mellyana Dhian’s novel Pangeran Hati. The method used in this research is descriptive qualitative. The data in this study are  wiritten data in the from text containing educational values in the novel Pangeran Hati by Mellyana Dhian. Research result – Based on the research results it can be concluded that the value of education in the novel Pangeraan Hati by Mellyana Dhian includes the value of religious educationincludes praying, having good prejudice, advising in goodness, worship, giving thanks. then the value of moral education includes good morals dan bad morals. Good morals include helping, respecting older people, maintaning honor, forgiving, and being humble. while bad morals include selfish, oppresive, and lying. Then the social value of mutual respect by maintanning dood manners and living in harmony between religious communities. Then the value of cultural education includes customs and traditional songs. The valueeducation in movel Pangeran Hati by Mellyana Dhian is very important for students to emulate in their daily lives. The value of education is views that are able to shape a person’s character for the better. The novel Pangeran Hati by Mellyana Dhian contains educational values consisting of religious education values, morl education value, social education value, and culture education value which are very beneficial for readers, both students and society in general.